Valoración de hormonas esteroides en heces de una pareja de lobo mexicano (Canis lupus baileyi) en cautiverio - Soto, María A.; Salame-Méndez, Arturo; Ramírez-Pulido, José; Yañez, Lourdes; Armella, Miguel Angel (Instituto de Ecología, A.C., 2020)
The Mexican Gray Wolf (Canis lupus baileyi) is one of the most distinctive groups of wild canids.It has been erradicated from most of its original range and there is no solid evidence of wild populations. All known individuals of this species are kept in zoos or special enclosures. Recently a great deal of efforts have been done in oder to reintroduce this subespecies to its natural habitat. Studies on this species are focused on the behavior and socialstructure, but there are few on the reproductive physiology. In this paper we analyze progesterone (P4), testosterone (T) and estradiol (E2) concentrations in feces of a pair of Mexican grey wolves during the Winter and Spring. Steroids were quantified by enzime immunoassay and evaluated using a micro titer plate. We tested the use of hormone levels to determine gender of the animals and found T to be useful. In the male, P4 levels had a cyclic pattern with peaks in January and February that coincided with cyclic variation in T. E2 did not show significant changes. In the female, P4 showed a cyclic pattern with fluctuations from January to April, T followed the same pattern, and E2 peaked in January, February, and April. The peak of February ended with a rise in P4. These results suggest that concentrations of sexual steroid hormones are in general high during the reproductive period.